(untitled) (Scientific journal of the Fergana State University, 2024)
This article analyzes the personnel working in the press system of the Turkestan ASSR, their national composition. One of the main issues is the system of personnel training, their qualification improvement and retraining. Correct implementation of this policy is a decisive factor in the success of the problem and solution. In this case, the national structure of the employees in the field of the press was studied in comparison with the personnel structure of other state bodies in TASSR.